Eksocentriske kompositas plads blandt andre typer af komposita - Szubert, Andrzej (Folia Scandinavica Posnaniensia, 2010)
The article presents several classifications of compounds followed by the author’s suggestions regarding a new classification. The author discusses definitions of exocentric compounds put forward by various scholars and proposes a new definition of exocentric compounds.